La memoria de la Madre Tierra: el canto ecológico de los poetas mapuches - Fierro, Juan Manuel; Geeregat V., Orietta (Anales de Literatura Hispanoamericana, 2004)
The article studies the problem of memory, the link with nature and ecological concerns, as textualised in the poetic works of contemporary Mapuche writers. These texts form a manifesto in which nature is presented, revealed and kept alive, appealing to lyrical enunciation so as to be able to receive nature, hear its voice and multiply its lament and its hope. Written against all odds, Mapuche poetry is the result of a permanent contemplation, within which memory becomes a bridge between dream and reality, between country and city, between life and yearning, between man and the spirit of nature whose maternal dimension it strives to recover.